Burnout among house officers in Myanmar: A cross-sectional study. (September 2018) - Lin, Kyaw San; Zaw, Thant; Oo, Win Min; Soe, Pa Pa
Abstract: Background: Burnout can result in a serious negative impact on a doctor's life, the quality of patient care, and the healthcare organization. This study aims to determine the prevalence of burnout and factors affecting burnout among the house officers in Myanmar. Materials and methods: An exploratory cross-sectional quantitative survey study was conducted using a self-administered, web-based survey. House officers working in any of the government hospitals in Myanmar were invited to participate in the study. The survey link was distributed online via Facebook. To measure burnout, we utilised a non-proprietary single-item measure, validated to serve as a reliable substitute for the Maslach Burnout Inventory Emotional Exhaustion (MBI:EE). To measure global life satisfaction, the validated Satisfaction with Life Scale (SWLS) was used. The questions for the scales regarding the psychosocial environment were extracted from the long version of the validated Copenhagen Psychosocial Questionnaire (COPSOQ II). The scales selected were "possibilities for the development", "meaning of work", "commitment to workplace", "recognition", "social support from colleagues" and "social support from supervisors". Multiple logistic regression method was applied to determine the factors associated with burnout. Results: Regarding the prevalence of burnout, out of 159 participants, 42.8% (n = 68) of the participants had no symptoms of burnout. 57.2% (n = 91) had one or more symptoms of burnout. Multivariate analysis showed that the only significant factor associated with burnout was "recognition" (OR 0.96, 95% CI: 0.94–0.97, P < 0.001). Conclusion: From this study, we have determined the relatively high burnout prevalence and that recognition is the only preventive factor; increase in recognition will decrease the odds of burnout. Hence, urgent interventions are recommended to prevent undesirable effects on both health professionals and patients. Recognition for work done should always be in the heart of the health authorities and medical community in Myanmar. Highlights: We found a relatively high burnout prevalence among the house officers in Myanmar. Recognition was the only significant preventive factor against burnout. Increase in recognition will decrease the odds of burnout.